Sodium-dependent effects of melatonin on membrane potential of neonatal rat pituitary cells - Vanecek, J; Klein, D C (Endocrinology, 1992)
Melatonin inhibits GnRH-stimulated release of LH from neonatal rat pituitary cells, probably by inhibiting GnRH-induced elevation of intracellular Ca2+. This effect of melatonin seems to involve inhibition of Ca2+ influx through voltage-sensitive channels. Accordingly, it is possible that melatonin could act by hyperpolarizing pituitary cells, which would close these channels. This issue was addressed here by determining if melatonin influences membrane potential. Membrane potential and intracellular Ca2+ were studied in neonatal rat pituitary cells in suspension, using bis-oxonol and Fluo-3 as fluorescent indicators, respectively. It was found that treatment with melatonin alone causes membrane hyperpolarization and that it has a repolarizing effect after GnRH-induced membrane depolarization. This effect on membrane potential appears to be mediated by high affinity melatonin receptors and a pertussis toxin-sensitive Na(+)-dependent mechanism; it is not dependent upon Ca2+, Cl-, or bicarbonate. This may be the molecular basis of action of melatonin in other tissues with high affinity melatonin receptors.
Keywords: Receptors, Melatonin; receptory neurotransmiterů; Aging; Rats; Cell Membrane; novorozená zvířata; inbrední kmeny potkanů; Membrane Potentials; melatonin; Virulence Factors, Bordetella; stárnutí; vápník; membránové potenciály; melatoninové receptory; Gonadotropin-Releasing Hormone; Animals; Calcium; hormon uvolňující gonadotropiny; Animals, Newborn; Pertussis Toxin; pertusový toxin; zvířata; fluorescenční barviva; Pituitary Gland; Rats, Inbred Strains; Receptors, Neurotransmitter; krysa rodu Rattus; faktory virulence rodu Bordetella; Fluorescent Dyes; Sodium; ženské pohlaví; buněčná membrána; Female; sodík; hypofýza; Melatonin